PENGARUH IKLAN/AKTIF SOSIAL MEDIA, WORD OF MOUTH, DAN PELAYANAN TERHADAP KEPUTUSAN MUZAKKI DALAM MEMBAYAR ZAKAT (STUDI KASUS LEMBAGA AMIL ZAKAT SAHABAT MUSTAHIQ KOTA KEDIRI) - Ardiansyah, Febrico Candra; Muttaqin, Aminnullah Achmad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The collection of zakat in Indonesia has significantly increased from 2020 to 2022, but it has not yet met the expected targets. This study identifies the factors influencing muzakki decisions in paying zakat at the Amil Zakat Institution (LAZ) Sahabat Mustahiq in Kediri City, namely advertising, social media activities, word of mouth, and service. This research uses a quantitative approach with explanatory research. Primary data was collected from 112 active muzakki respondents selected randomly and analyzed using multiple linear regression methods with the help of SPSS. The findings show that advertising, social media activities, word of mouth, and service significantly influence muzakki decisions in paying zakat. The conclusion of this study highlights the importance of communication strategies and service quality in maximizing zakat potential. The implication of this research is that increasing public awareness about zakat and its management can support government programs in reducing poverty. This study contributes to understanding muzakki behavior and can be used as a reference for LAZ in optimizing zakat collection through effective marketing strategies. Kata Kunci : Keputusan Muzakki; Zakat; Iklan; Media Sosial; Word of Mouth; Pelayanan